Real world outcomes of iodinated contrast media re-exposure in Chinese patients with prior hypersensitivity - Sainan Bian; Lun Li; Le Cui; Zhirong Du; Lu Lyu; Yi Ru; Zixi Wang; Kai Guan (Allergy, Asthma & Clinical Immunology, 2026)
Abstract Background To investigate the clinical outcomes of patients with a history of iodinated contrast medium (ICM)-induced hypersensitivity reactions (HSR) undergoing re-exposure to ICM. Methods Medical records of inpatients who received allergy consultations in Peking Union Medical College Hospital from January 1, 2019 to July 31, 2024 were retrospectively reviewed. Patients with prior ICM-related HSR who subsequently underwent ICM re-administration were enrolled. Results Of 997 patients referred for allergy consultation, 65 met inclusion criteria, including 47 males (72.3%) with a mean age of 59.6 ± 16.1 years. Twenty-eight patients (43.1%) had previous non-immediate HSR, who were more likely to receive iodixanol than those with prior immediate HSR. In total, 55 patients (84.6%) received premedication before ICM re-exposure, and 33 (50.8%) underwent ICM switching. Following ICM re-exposure, recurrent HSR occurred in 6 patients (9.2%), including 2 immediate and 4 non-immediate reactions, while 59 patients (90.8%) had no recurrence. The proportion of prior non-immediate HSR was significantly higher in patients with recurrent HSR than those without (100% vs. 52.5%, P = 0.025). The HSR recurrence rate was lowest among patients who underwent ICM switching combined with premedication, compared with patients receiving premedication without ICM switching and those receiving ICM switching without premedication (0.0% vs. 33.3% vs. 14.3%, P = 0.021). Conclusions Most patients with a history of ICM-related HSR safely tolerate ICM re-administration when managed with ICM switching, premedication, or a combination of both. This real-world study provides valuable clinical reference for the management of ICM re-exposure, especially in medical centers where ICM allergy test is not routinely available.